2006
DOI: 10.1080/10903120600884863
|View full text |Cite
|
Sign up to set email alerts
|

Taser Use in Restraint-Related Deaths

Abstract: This is the largest review of Taser-related fatalities reported in the medical literature. The findings are consistent with prior studies, suggesting a high frequency of restraint-related and excited delirium-related fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(45 citation statements)
references
References 18 publications
2
42
0
1
Order By: Relevance
“…17,18 Most reported subjects were agitated young males, often chronic and acute users of stimulant or psychoactive drugs, who collapsed while being restrained. [19][20][21][22][23] A recent European publication confirms the international nature of this problem. 24 Initial studies focused on methods of restraining or subduing subjects, 17,23 providing few data regarding cardiac rhythms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Most reported subjects were agitated young males, often chronic and acute users of stimulant or psychoactive drugs, who collapsed while being restrained. [19][20][21][22][23] A recent European publication confirms the international nature of this problem. 24 Initial studies focused on methods of restraining or subduing subjects, 17,23 providing few data regarding cardiac rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…However, our subjects had demographic and drug-use profiles similar to those of subjects we excluded because of insufficient data, subjects identified by prospective study of nonfatal use of CEWs by law enforcement, 30,37 and subjects in prior reports of sudden deaths during law enforcement interactions-either associated 21 or unassociated with use of CEWs. 18,19,24 At autopsy, the overall incidence of moderate and marked heart disease was 45%, not statistically different from the 54% reported for subjects who died within 24 hours of CEW discharge 21 (p = 0.50). These considerations suggest that our subjects are in fact representative, but do not exclude undetected bias.…”
Section: Methods Of Identifying Subjectsmentioning
confidence: 99%
“…In cases of recorded deaths, the mode of death had never been established, though a state of "excited delirium" has been reported. 21 However, excited delirium has not been listed as a cause of sudden cardiac death in the arrhythmia literature.…”
Section: Evidence That Stun Guns Cannot Stimulate the Heartmentioning
confidence: 99%
“…1 Studies examining the safety of TASER use in healthy volunteers have suggested that the electrical current produced by such devices does not result in any sustained clinically significant cardiac, respiratory or physiologic stress. [2][3][4] Nevertheless, injuries 5,6 and deaths 7,8 have been reported with the use of TASERs. We report the case of a traumatic globe rupture and associated vitreous hemorrhage, retinal laceration and lid injury resulting from the use of a TASER by law enforcement officials.…”
Section: Introductionmentioning
confidence: 99%